(untitled) (Hungarian Journal of Industry and Chemistry, 2011)
This paper deals with the determination of the inductance of starter relays. The article proposes a method for the electromechanical determination of the self-inductance of the electromagnet and its derivative for various positions of the iron core. The results obtained at different current levels are given in tables and figures.